Improving the technological preparation of centerless grinding operations - Malinin, Pavel; Bochkarev, Petr; Ulyanova, Larisa; Shalunov, Vycheslav (Известия высших учебных заведений. Поволжский регион:Технические науки, 2023)
Background. Centerless grinding, as a method of finishing machining of parts such as bodies of revolution, combining high efficiency and accuracy of processing, is widely used in modern machine-building enterprises, where parts are produced in large batches. However, the expansion of its use requires a serious improvement in technological preparation. Materials and methods. The article presents an approach to the structural classification of centerless grinding methods, aimed at grouping them according to the homogeneity of the design procedures for technological support. Grouping of schemes for centerless grinding was carried out as a target task of determining the rational number of groups to be created with the maximum use of the same methodological approaches and models for designing technological processes. Results. The developed formalized models made it possible to scientifically substantiate the sequence of formation of clusters of processing schemes for specific production conditions. The results of grouping processing methods for design procedures for assigning technological modes of centerless grinding operations are presented. Conclusions. A new approach is described in relation to the design of centerless grinding operations based on their classification according to the proposed criteria, taking into account the real state and capabilities of production systems.